Developing Metacognitive and Discursive Activities in The Indonesian Mathematics Education - Kaune, Christa; Fresenborg, Elmar Cohors; Nowinska, Edyta; Marpaung, Yansen; Handayani, Novi (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2012)
This article reports on the findings of a German-Indonesian feasibility study, which has been conducted to examine whether a more extensive pilot study could be successful. The objective of the pilot study is to enhance the mathematical skills of Indonesian students in the 7th class by increasing the number of students who can really understand the mathematical concepts and methods introduced in class. In order to achieve this, a learning environment for the introduction of integers was designed and implemented in class. During its implementation, a teaching style has been practised which encourages metacognitive and discursive activities in the students. In this paper the theoretical background for the construction of a comparing test is set out, several exercises are presented as examples and on the basis of student solutions, taken from the test, the effects of the innovative teaching is demonstrated.Â